Bond strength comparison among 10-MDP-containing and non-10-MDP-containing adhesives in different degrees of dental fluorosis = Comparación de fuerza de unión entre adhesivos que contienen y no contienen 10-MDP en diferentes grados de fluorosis dental - Solís Martínez, Luis Javier
Dental fluorosis can cause changes in the enamel surface, conditioning its functionality and esthetics. The application of dental adhesives is a treatment option; however, their use on fluorotic teeth can result in limitations. The aim of this study was to compare the shear bond strength of two different adhesives, one with 10-MDP and one without 10-MDP, in different degrees of dental fluorosis.This is an in vitro study on dental enamel samples, a total of 180 samples with the inclusion criteria were treated, randomly divided into two groups of 90, according to the type of dental adhesive, where each group was again divided into three groups of 30 samples, representing different degrees of dental fluorosis according to the Thylstrup-Fejerskov index (Group I: TF1 and TF2; Group II: TF3; Group III: TF4). Normality tests, two-factor ANOVA, and post-hoc tests were used to determine differences between the groups, with a significance level of 95%. As results, a statistically significant difference was shown between the use of dental adhesive with 10-MDP and the three groups of dental fluorosis (p=0.011), in addition, a Tukey post-hoc test on the groups treated with 10-MDP adhesive revealed a statistically significant difference between group I versus group II, and group I versus group III, (p=<0.05). It is concluded that the use of adhesive systems with 10-MDP presents a better shear bond strength on enamel with dental fluorosis grades I and II in the Thylstrup-Fejerskov index.